Have fun and celebrate in the social dynamic: Festivals, fairs and cultural fronts - Gonzáles, Jorge (1989)
From research, the question is in rethinking and changing the ways of approaching and structuring our objects of study. Worth the same for the analysis of the holidays. In this way, attention should be paid not only to differences, distinctions and differences in the plurality of cultures coexisting in a given social formation, but also precisely on the basis of these distinctions (of class, of groups, of ethnic groups, of age, of sex, etc.) allow us to think in different scales, the construction of similarities, convergences, borders and differential identities within a class structure.